INOVASI MANAJEMEN KESISWAAN DALAM INTERNALISASI KARAKTER SISWA: STUDI KUALITATIF DI TK KHADIJAH 65 GENTENG BANYUWANGI - Imam Wahyono; Ahmad Aziz Fanani; Lailatul Usriyah; Eka Ramiati; Achmad Dhawamun Nawafil (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Character education from an early age is important in shaping a generation that is moral, religious, and independent. However, the way character is shaped in schools still feels formal and is not yet integrated into student management. This study aims to innovate student management at TK Khadijah 65 Genteng Banyuwangi in order to implement religious values and early childhood independence, as well as to analyze how the planning, habituation, and evaluation of student programs are systematically designed and implemented to shape the character of early childhood students. This study uses a qualitative approach with a case study method, with subjects consisting of the principal, teachers, parents, and TPQ partners. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model, as well as triangulation as a means of ensuring the validity of the research results. The results showed that student management at Khadijah 65 Kindergarten covered four main aspects: (1) planning based on the school's vision and involving the participation of all parties, (2) the implementation of religious habits and independence through routine activities, (3) character development assessment using checklists and portfolios, although not yet fully uniform, and (4) strong cooperation between the school, parents, and TPQ, which reinforces good habits at home and in the surrounding environment. This study concludes that the innovation in student management at Khadijah 65 Kindergarten has succeeded in creating a comprehensive character education environment, but standardization of assessment tools and improvement of teacher skills are needed to ensure the program continues to develop.